2021
DOI: 10.1002/anie.202113895
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Triazolate‐Framework‐Derived FeN4Cl1 Single‐Atom Catalysts with Hierarchical Porosity for the Oxygen Reduction Reaction

Abstract: The construction of single-atom catalysts (SACs) with high single atom densities, favorable electronic structures and fast mass transfer is highly desired. We have utilized metaltriazolate (MET) frameworks, a subclass of metal-organic frameworks (MOFs) with high N content, as precursors since they can enhance the density and regulate the electronic structure of single-atom sites, as well as generate abundant mesopores simultaneously. Fe single atoms dispersed in a hierarchically porous N-doped carbon matrix wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
107
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 43 publications
3
107
0
Order By: Relevance
“…FeN 4 Cl 1 /NC exhibited a more favorable thermodynamic reaction process for ORR due to the improved adsorption energy for OH* (Figure 8d-f). [103] Recent reports have demonstrated that the OH* could graft to FeN 4 dynamically during the ORR process, and the formed FeN 4 OH can act as the efficient active sites to facilitate the last step desorption of OH*, leading to enhanced ORR activity. [104,105] The OH* can also boost the catalytic activity of FeCoN 5 dual atom sites anchored on N-doped carbon electrocatalyst.…”
Section: Guest Group Engineering Carbon-supported Sacsmentioning
confidence: 99%
See 2 more Smart Citations
“…FeN 4 Cl 1 /NC exhibited a more favorable thermodynamic reaction process for ORR due to the improved adsorption energy for OH* (Figure 8d-f). [103] Recent reports have demonstrated that the OH* could graft to FeN 4 dynamically during the ORR process, and the formed FeN 4 OH can act as the efficient active sites to facilitate the last step desorption of OH*, leading to enhanced ORR activity. [104,105] The OH* can also boost the catalytic activity of FeCoN 5 dual atom sites anchored on N-doped carbon electrocatalyst.…”
Section: Guest Group Engineering Carbon-supported Sacsmentioning
confidence: 99%
“…[99][100][101] For example, the halogen atom (Cl − ) coordinated with Fe-N 4 plane vertically (FeCl 1 N 4 ) has shown improved oxygen adsorption capacity, leading to boosted ORR performance. [102,103] Similarly, by the pyrolysis of metal (Zn/Fe)triazolate (MET) frameworks decorated with 4,5-dichloroimidazole, FeN 4 Cl 1 species anchored on N-doped porous carbon matrix (FeN 4 Cl 1 /NC) electrocatalyst was obtained (Figure 8a). FeN 4 Cl 1 /NC exhibited an outstanding ORR performance with a half-wave potential (E 1/2 ) of 0.91 V versus RHE in 0.1 m KOH (Figure 8b,c).…”
Section: Guest Group Engineering Carbon-supported Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past couple of years, various SMACs have been therefore widely explored and showed encouraging electrocatalytic ORR activities [ 29 32 ]. The high intrinsic activity of isolated metal sites and the low cost of component elements in SMACs make these catalysts promising candidates to substitute traditional noble metal-based ORR catalysts [ 33 37 ]. Particularly, carbon-based SMACs exhibit the state-of-the-art electrocatalytic ORR activities, and have been accordingly recognized as an emerging type of ORR catalysts for potential practical applications in fuel cells and metal-air batteries [ 38 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…On account of the periodic porosity and tunable structural characteristic, versatile functionality, chemical/thermal stability, and high surface area, MOFs hold great potential as multifunctional platforms for theranostics [ 44 46 ], catalysis [ 47 , 48 ], gas storage and separation [ 49 , 50 ], energy storage and conversion [ 51 , 52 ], optoelectronics [ 53 , 54 ], etc. Significantly, due to the distinct characteristics of tunable luminescence [ 55 ], optical absorbance [ 56 ], conductivity [ 57 ], and catalytic activity [ 58 , 59 ], MOFs have also been widely exploited for the development of various sensors in recent years [ 60 64 ].…”
Section: Introductionmentioning
confidence: 99%